Reinterpreting Waqf in Light of Contemporary Socio-Economic Realities - Shafa'at Ahmad Aliyu; Adamu Abubakar Muhammad; Adam Muhammad Ardo; Maryam Adam (IDRIS Darulfunun Institute, 2025)
Waqf (Islamic endowment) has historically been a key driver of socioeconomic development in Muslim cultures, funding education, healthcare, social welfare, and public infrastructure. However, conventional waqf administration and utilization strategies have struggled to adequately address modern socioeconomic concerns like as poverty, unemployment, urbanization, financial isolation, and inadequate institutional governance. This research investigates the importance of reinterpreting waqf within the context of present socioeconomic realities while maintaining true to its classical juristic roots. The study uses a qualitative and analytical approach on Qur'anic principles, Prophetic traditions, classical fiqh literature, and modern Islamic finance scholarship to explore how waqf can be revitalized through innovative instruments, institutional reforms, and integration with modern economic systems. The research advocates for a maq??id al-shar??ah-oriented reinterpretation of waqf, which provides for greater flexibility in asset management, investment strategies, and governance structures while maintaining its perpetual and benevolent nature. The findings demonstrate the ability of contemporary waqf models such as cash waqf, corporate waqf, waqf-based social finance, and public-private partnerships to satisfy current developmental requirements in a sustainable manner. The research concludes that reinterpreting waqf in light of current socioeconomic conditions is not a departure from Islamic tradition, but rather a necessary evolution that can reposition waqf as a dynamic tool for inclusive growth, social justice, and sustainable development in today's Muslim world.